Peran Permainan Tradisional dalam Meningkatkan Motorik Kasar Anak Usia 5-6 Di RA Al Fattah Pacing Parengan Tuban - Ahmad Farid Utsman; Roudlotun Ni'mah; Rohana Rohana (Al Ulya: Jurnal Pendidikan Islam, 2018)
Physical motor development is one of the most important factors in the overall development of individuals. The effectiveness of the application of traditional games (crank) in stimulating the gross motor nerves of children because in traditional games the child will use his physical abilities in playing. In addition, traditional games (crankshaft) can be used as cultural heritage, because in order for them to know it turns out traditional crank games are the original game of their ancestors, and this sustainability game must be maintained so that traditional crank games are not extinct and forgotten.This study aims to determine how the role of traditional games in improving gross motor skills in RA Al Fattah Pacing students in Tuban. To answer the big question the author uses qualitative research methodology with data search methods using Observation, Documentation, and Interview. Then the data obtained will be analyzed by data triangulation (source and technique) The results showed that: 1) Traditional games (crankshaft) were instrumental in increasing the gross motor skills of RA Al Fattah Pacing Parengan Tuban students, this can be seen from the indicators of the many achievements of RA students at festivals and related competitions with the gross motoric abilities of children, 2) to improve students' gross motoric skills on an ongoing basis, educators continue to hone the gross motoric skills of students by continuing to make crank line pattern patterns with varied variations.